INDUSTRIAL PERSPECTIVE ON MICRO-CREDENTIALS: A COMBINED SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Johan, Riche Cynthia; Purwoningsih, Tuti; Rullyana, Gema; Wihardini, Diah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to explore the development and application of micro-credentials (MCs) as an alternative, competency-based learning model increasingly adopted in higher education and industry. Micro-credentials represent an alternative, competency-based learning model increasingly adopted in higher education and industry. The method used is a combination of a systematic literature review (SLR) and bibliometric analysis, designed to examine research trends, learning models, curriculum structures, and skill areas associated with micro-credentials. Data from 482 documents indexed in Scopus and Web of Science (WoS) from 2008 to 2023 were analyzed. The findings reveal a growing global interest in MCs, particularly in digital, information, and technical skills fields. The bibliometric analysis highlights the United States as the leading country in micro-credentials research, followed by Australia and the United Kingdom. The thematic analysis identifies four primary learning models used in micro-credentials: Project-Based Learning (PBL), Self-Directed Learning, Problem-Based Learning, and Game-Based Learning. Additionally, micro-credentials curriculum structures often adopt modular, blended, and online formats to offer flexible, accessible learning pathways. Industry engagement is critical in MC, ensuring curriculum relevance to workforce needs through collaborations that define skill requirements, offer internships, and co-develop assessments. Micro-credentials evaluation methods focus on competency-based assessments, including portfolios and direct performance evaluations, providing practical evidence of learners’ skills and readiness for professional roles. The implication of this study is to provide a structured foundation for institutions and policymakers to design more effective, standardized, and industry-aligned micro-credential programs, while encouraging further research on long-term outcomes, transferability, and recognition across education and labor systems.